The impact of transaction costs on the participation of smallholder farmers and intermediaries in the banana markets of Burundi, Democratic Republic of Congo and Rwanda - Machethe, Charles Lepepeule (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.